Analisis Perilaku “CERDIK PTM” dengan Pendekatan Theory of Planned Behavior untuk Pencegahan Hipertensi pada Remaja di Kota Jayapura - Adimuntja, Natalia Paskawati; Nabuasa, Christin Debora; Asriati, Asriati; Pamangin, Lisda Oktavia Madu; Nurdin, Muhammad Akbar; Maturbongs, Margaretha Rosari (LPPM Hang Tuah Pekanbaru, 2025)
The prevalence of hypertension in Jayapura City is 35.03% (1). Implementation of CERDIK PTM behavior for adolescents is important to improve health status, efforts to improve clean and healthy living behavior, monitoring and early detection of NCD risk factors. This study aimed to determine the factors related to the behavior of